The Effectiveness of Using Hand Puppet in Teaching Speaking - Moka, Suciati Faradilla Arafiah; Ma'rifatulloh, Sayid (Teaching English as Foreign Language, Literature and Linguisticss, 2022)
In this study, the researcher attaches several research problems. Before the treatment, students' ability to speak was still lacking because students were still studying speaking lessons in the usual way, such as only explaining the material and practicing speaking without media. After the treatment, the students' abilities were further improved because they were taught speaking lessons by practicing using the Hand Puppet media. There was a significant difference, namely the increasing ability of students. Students are more straightforward in speaking when using the Hand Puppet media. Researchers used the pre-experimental method to obtain score data. Researchers conducted a normality test to find out whether the data was normal or not. Based on the normality test of the data that has been carried out by the researchers, it shows that sig. 2-tailed is 0.200 meaning that the data is normally distributed, followed by a simple paired t-test. based on the Testing of Hypothesis Terms, If the value of t is sig. <0.05, Ha is accepted and H0 is rejected. on the simple paired t-test calculation, the data shows sig. (2-tail) 0.000. The data is smaller than 0.05, meaning that H0 is rejected and Ha is accepted.